Clinical patterns and causes of post-cholecystectomy syndrome - Muhammad, Muhammed Ihsan; Alhassan, Abdullah Hasem; Alkhars, Abdulmohsen Yaseer; Alzahrani, Rayan Abdulkhaliq; Mansour, Mohammed Hamad Al; Alghamdi, Fares Hamoud; Almarri, Mohammad Saleh; Ghzoi, Fatimah Ali; Alwadai, Rakan Hamad; Aljarallah, Mohannad Yousef; Saihb, Abdullah Ahmed (International Journal Of Community Medicine And Public Health, 2021)
Post-cholecystectomy syndrome is suspected when the patients complain about the persistent presence of pain in the right upper abdominal quadrant. Other symptoms might appear which are related to the gastrointestinal tract. These symptoms appear after performing cholecystectomy. The manifestations are usually similar to those experienced before the procedure. In this study, the aim to conduct a literature review to increase the knowledge and to explore facts related to the clinical patterns and causes of post-cholecystectomy syndrome. The most commonly reported cause of this syndrome is the prior development of an extra-biliary disorder, which includes many modalities as peptic ulcer, reflux esophagitis, chronic pancreatitis, irritable bowel syndrome, and biliary-related disorders. However, the etiology of postcholecystectomy is hugely variable across the different studies in the literature. Patients that develop postcholecystectomy syndrome usually present with non-specific gastrointestinal symptoms that may or may not be similar to the symptoms that were exhibited before conducting the surgery. Some of the common physiological changes that have been reported with postcholecystectomy syndrome include the disruption of cholecysto-antral reflex, the cholecystosphincter of oddi reflex, and the cholecysto-esophageal related reflexes. In addition, the development of other changes that can significantly affect the normal physiology of the gastrointestinal tract leads to the development of significant symptoms and clinical patterns.